IN VITRO ANTIHEMOLYTIC AND ANTI-ARTHRITIC ACTIVITIES OF ARISTOLOCHIA BRACTEATA (Lam.) - SABARNA, T.; VIDHYA, R. (Innovare Journal of Ayurvedic Sciences, 2017)
Background: Aristolochia bracteata (Lam.) is described in Ayurveda for the treatment of painful inflammations, cardiac disorders. Objectives: The present study was aimed to investigate the phytochemical, in vitro antihemolytic and anti-arthritic activities of ethanolic extracts of leaf, stem and root of A. bracteata. The phytochemical, in vitro antihemolytic and anti-arthritic activities of different parts of A. bracteata by standard protocols. Results: The various bioactive phytocompounds such as carbohydrates, flavonoids, saponins, steroids and coumarins present in leaf, stem and roots of A. bracteata. The maximum protection of RBC membrane lysis was observed in ethanolic extract of A. bracteata. The ethanolic extracts of stem exhibited significant protection of membrane denaturation and proteinase inhibitory activities. Â Conclusion: So, from this result indicates A. bracteata may be used in designing various pharmacological drugs and treatment of rheumatoid arthritis.Â